2006
DOI: 10.5713/ajas.2006.1033
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Elasticity and Induction of Heat Shock Protein 70 in Labeo rohita Acclimated to Three Temperatures

Abstract: The metabolic response of Labeo rohita to thermal acclimation was assessed. Advanced fingerlings of L. rohita (average weight 31±1.4 g) were acclimated to 31, 33 and 36°C compared with ambient temperatures (26°C) for 30 days and different enzymes associated with stress response were estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 39 publications
6
16
0
Order By: Relevance
“…The AST and ALT enzyme activities increased with the heat shock, which in turn converts amino acid to an intermediate, which can enter TCA cycle and finally produce ATP to cope up with the stress. Similar results were also reported by Das et al (2006) in L. rohita exposed to different temperatures and by Vijayan et al (1997) in tilapia exposed to confinement stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The AST and ALT enzyme activities increased with the heat shock, which in turn converts amino acid to an intermediate, which can enter TCA cycle and finally produce ATP to cope up with the stress. Similar results were also reported by Das et al (2006) in L. rohita exposed to different temperatures and by Vijayan et al (1997) in tilapia exposed to confinement stress.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, there was a significant increase in MDH activity in fishes after heat shock, which strengthens the above hypothesis. This is supported by the findings of Das et al (2006), who found elevated MDH activity in fishes acclimated at higher temperature.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Medaka (Orizias latipes) embryos were unable to induce stress protein synthesis in earlier stages and were more susceptible to heat shock than embryos at later stages where HSP induction was observed (Werner et al 2001). Das et al (2006) reported an increase in the inducible form of HSP70 in the liver tissue of L. rohita acclimated to three temperatures (31, 33 and 36°C) and suggested that the increased level of HSP70 was responsible for the increase in thermal tolerance with increasing acclimation temperatures in L. rohita . Similarly, the increase in the thermal tolerance with increasing acclimation temperature observed in the present study suggests that the increase in the HSP70 renders H. brachysoma more thermotolerant with increasing acclimation temperature.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, expression of Hsp genes during A. hydrophila served a dual response to infection and stress. The modulation of Hsp70 was investigated in rohu during temperature change (Das et al 2006) and starvation (Yengkokpam et al 2008). However, no study has yet revealed the modulation of this or any other genes of this family during bacterial infection in rohu.…”
Section: Introductionmentioning
confidence: 99%